1995
DOI: 10.1038/bjc.1995.418
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for mutual interdependence of epithelium and stromal lymphoid cells in a subset of papillary carcinomas

Abstract: Summary We have correlated the morphological features of 30 human thyroid carcinomas with the cellular localisation of insulin-like growth factor 1 (IGF-1) mRNA and IGF-1 receptor peptide using in situ hybridisation with digoxigenin-labelled oligoprobes and immunohistochemistry. Four of the five follicular carcinomas studied showed a consistent, uniform, strong positivity for IGF-I mRNA in tumour cells compared with weakly positive surrounding normal follicular tissue and negative stroma. The majority of papil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…Eosinophilic changes in the tumor cells and a background complication of thyroiditis are not necessarily essential features in this disease. It has been reported that plasma cells within tumor stroma produce insulin‐like growth factor (IGF)‐1, which acts on follicular epithelial cells that have IGF‐1 receptors, thereby inducing formation of tumor tissue 19 . It is also presumed that the interaction between the stroma and tumor cells forms WLTT 20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eosinophilic changes in the tumor cells and a background complication of thyroiditis are not necessarily essential features in this disease. It has been reported that plasma cells within tumor stroma produce insulin‐like growth factor (IGF)‐1, which acts on follicular epithelial cells that have IGF‐1 receptors, thereby inducing formation of tumor tissue 19 . It is also presumed that the interaction between the stroma and tumor cells forms WLTT 20 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that plasma cells within tumor stroma produce insulin-like growth factor (IGF)-1, which acts on follicular epithelial cells that have IGF-1 receptors, thereby inducing formation of tumor tissue. 19 It is also presumed that the interaction between the stroma and tumor cells forms WLTT. 20 Further studies are needed to investigate this, and accumulation of similar cases is also needed.…”
Section: Discussionmentioning
confidence: 99%
“…For this study, one 5-μm paraffin section was cut from each of the five TMA blocks and stained with antibodies for IGF1R(22–24). Immunostaining was performed in a single staining run on a Dako Autostainer (Dako Corporation, Carpinteria, CA).…”
Section: Methodsmentioning
confidence: 99%
“…nodular goitre) associated with thyroiditis; this group includes a subset of papillary carcinomas with dense stromal lymphoplasmacytic infiltrate, and large, pink granular neoplastic cells [3]. It has been advanced that in this setting the immune response and cytokine(s) production may also be associated with growth stimulation [58].…”
Section: Mitochondrion-related Alterations In Tumours With and Withoumentioning
confidence: 99%